Purchasing Intension: Effect of Shopee Paylater and Shopee Loans Features - Sugito, Pudjo; Yulehinin, Firsty; Kamaluddin, Kamaluddin; Nirwana, Nirwana (Business Management Research, 2023)
The aim of this study was to investigate how shoppe paylater and shoppe loan features affected purchasing intent. To determine which of the two independent research factors had the greatest influence on purchasing interest. This study's population consists of Merdeka University Malang students. To acquire primary data, a simple random sample procedure was applied. There were 80 students who responded. The primary data was also analyzed using the structural equation model-SmartPLS. According to these findings, the Shopee Paylater and Shopee Loans features have a significant impact on purchase intention both partially and simultaneously. Interestingly, shopee loans have a dominant effect on purchasing decisions. However, the research findings still require external validity by conducting other studies with different populations to generalize the findings more broadly.